Levels of consciousness in psychopathology according to monitoring of neural network centers alpha rhythm rs-EEG - Lytaev, Sergey; Belskaya, Ksenia (Institute of Advanced Engineering and Science, 2025)
Consciousness is the highest mental function that integrates attention, memory, individual experience, emotions, and all modalities of perception, information processing and other manifestations of higher nervous activity of a person. This research was aimed to theoretically substantiate the functional connection of the brain alpha regulatory system with the modulation of conscious activity and to identify pathological electroencephalography (EEG) patterns of the alpha rhythm characterizing a decrease in the level of consciousness. 40 patients (main group) with current symptomatic schizophrenia associated with neurocognitive and depressive symptoms, and 38 healthy subjects (control group) were examined. Both nonspecific physical parameters of the alpha wave process–index, frequency and amplitude, and physiological features of alpha oscillations–regularity, auto rhythmicity (modulation) and stability of the EEG alpha rhythm were analyzed with using WinEEG, EEG Studio, and Loreta-Key viewer programs. A line of indicators for the alpha rhythm in schizophrenia have been calculated–based on coherence in different brain areas, the latent period (LP) of desynchronization, the average number of bursts and the tone of the cerebral cortex.